Wdrażanie podatków energetycznych i węglowych - Ptak, Michał (Implementing Energy and Carbon Taxes, 2005)
The paper presents the role of energy and carbon taxes which have already been introduced by a number of European countries. These taxes are often implemented as a part of environmental tax reform. Objective pursued by the reforms is not only environmental. Appropriately designed environmental tax reform may also increase economic growth and employment by overcoming some distortions in the economy.The author outlines the minimum level of energy taxation according to the Directive 2003/96/EC for the taxation of energy products and electricity. With the new Directive, the European Union intends to reduce existing distortions of competition between Member States and energy products as a result of divergent rates of tax on energy products. The Directive increases also incentives to use energy more efficiently.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 118-129